Wie die Materialengpässe den Arbeitsmarkt treffen; How Material Shortages are Affecting the Labour Market - Markus Hummel; Christian Hutter; Enzo Weber (Wirtschaftsdienst, 2022)
– Although industrial production in Germany picked up again significantly with the recovery from the Corona crisis, supply bottlenecks for raw materials and intermediate products such as semiconductors became increasingly noticeable over 2021. In this article, we examine how these obstacles affect the labor market development. To determine the extent and effects of the material bottlenecks, we use data from the ifo business surveys and from the statistics of the German Federal Employment Agency on manufacturing and construction. The results show that the impact of material shortages on unemployment is noticeable but still relatively limited. In contrast, there is a considerable effect on short-time work announcements. Apparently, short-time work is mainly used to adjust to the material shortages.
Keywords: J08; L70; 330; Arbeitsmarkt; Arbeitslosigkeit; Coronavirus; Deutschland